ISOTOPIC COMPOSITION OF SURFACE-CORRELATED CHROMIUM IN APOLLO 16 LUNAR SOILS - Kitts B.K.; Podosek F.A.; Nichols R.H.; Brannon J.C.; Ramezani J.; Korotev R.L.; Jolliff B.L. (My University, 2003)
We have analyzed by thermal ionization mass spectrometry (TIMS) the isotopic composition of Cr in five progressive etches of size-sorted plagioclase grains separated from lunar soils 60601 and 62281. Aliquots of the etch solutions were spiked for isotopic dilution (ID) analysis of Cr and Ca. The Ca ID data indicate that the initial etch steps represent dissolution of an average 0.1 to 0.2 μm depth from the grain surfaces, the approximate depth expected for implanted solar wind. The Cr/Ca ratio in the initial etches is several fold higher than that expected for bulk plagioclase composition, but in subsequent etches decreases to approach the bulk value. This indicates a source of Cr extrinsic to the plagioclase grains, surface-correlated and resident in the outermost fraction of a μm, which we provisionally identify as solar wind Cr. The surface-correlated Cr is isotopically anomalous and by conventional TIMS data reduction has approximately 1 permil excess 54Cr and half as great excess 53Cr. In successive etches, as the Cr/Ca ratio decreases and approaches the bulk plagioclase value, the magnitude of the apparent anomalies decreases approaching normal composition. If these results do indeed characterize the solar wind, then either the solar wind is enriched in Cr due to spallation in the solar atmosphere, or the Earth and the various parent bodies of the meteorites are isotopically distinct from the Sun and must have formed from slightly different mixes of presolar materials. Alternative interpretations include the possibility that the anomalous Cr is meteoritic rather than solar or that the observed (solar) Cr is normal except for a small admixture of spallation Cr generated on the Moon. We consider these latter possibilities less likely than the solar wind interpretation. However, they cannot be eliminated and remain working hypotheses.